MENGURAI BENANG KUSUT KESULITAN BELAJAR MURID KELAS 6 SDN 08 VII KOTO SUNGAI SARIAK DAN STRATEGI GURU DALAM MENINGKATKAN KEBERHASILAN BELAJAR - Dewi Fitriana; Putri Yulia Mandasari; Wendri Gusdi; Mulya Syafrina; Seri Sufani; Febrio Rozalmi Putra; Yusparni Yetti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to diagnose learning difficulties experienced by sixth-grade students at SDN 08 VII Koto Sungai Sariak. The diagnosis was conducted through direct classroom observation, interviews with teachers, and a literature review on indicators of learning difficulties. The results of the study show that several students have difficulties in understanding mathematical concepts, reading and writing, as well as critical thinking skills. The contributing factors include teaching methods that are not fully aligned with students' learning styles, lack of individual attention, and family background. These findings provide a basis for teachers to design differentiated learning strategies and appropriate interventions so that each student can achieve competencies according to curriculum standards.